UPAYA PBB DALAM MENYELESAIKAN KONFLIK UIGHUR DI XINJIANG - abdul rozzaq (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2023)
The Chinese government is suspected of committing human rights violations by eliminating race or ethnicity in the Xinjiang region permanently either directly or slowly. The international world and the United Nations are concerned about the Uighur tribe in Xinjiang, for the occurrence of human rights violations in the form of genocide. The author uses conflict theory, conflict resolution, human rights, human rights violations, and peace. While the research method, the authors use a descriptive research type based on secondary data sources in the form of related literature. Previously, researchers conducted research on previous research in collecting materials that would be used in this study. Researchers examined the conflict from late 2017 to October 1, 2022. Researchers found that the results of efforts to resolve the conflict failed because OHCHR could not work optimally because China often obstructed investigations on the grounds that it was their internal conflict.